Flexor Carpi Ulnaris Muscle Flap for Soft Tissue Reconstruction after Total Elbow Arthroplasty. (7th October 2014) - Okamoto, Syunro; Tada, Kaoru; Ai, Hachinota; Tsuchiya, Hiroyuki
Abstract : The soft tissue at the tip of the olecranon is very thin, leading to the frequent occurrence of wound complications after total elbow arthroplasty. To cover a soft tissue defect of the elbow, the flexor carpi ulnaris muscle flap is thought to be appropriate for reconstruction of the elbow with regard to its size, location, and blood supply. We got positive clinical results, so we report our experiences of using a flexor carpi ulnaris muscle flap for soft tissue reconstruction after total elbow arthroplasty.